Tunably fabricated nanotremella-like Bi2S3/MoS2: An excellent and highly stable electrocatalyst for alkaline hydrogen evolution reaction. (20th March 2020) - Zhou, Lianhong; Yang, Tiantian; Chen, Shouxian; Gao, Jun; Wang, Xuejiao; He, Ping; Lei, Hong; Yang, Dingming; Dong, Faqin; Jia, Lingpu; Jia, Bin; Zhang, Hui
Abstract: Reasonable design of efficient and stable catalysts with low cost and abundant natural reserves is vital for electrocatalytic water splitting. Herein, novel nanotremella-like Bi2 S3 /MoS2 composites with different mass ratios between Bi2 S3 and MoS2 have been successfully prepared through a hydrothermal approach and further applied to hydrogen evolution reaction (HER) in 1.0 M KOH electrolyte for the first time. When the mass ratio of Bi2 S3 and MoS2 is 5:5, as-prepared nanotremella-like Bi2 S3 /MoS2 (marked as BMS-5) manifests favorable HER catalytic activity with overpotential of 124 mV at current density of 10 mA cm −2 and relatively low Tafel slope of 123 mV dec −1 . Moreover, it exhibits an extraordinary durability for uninterrupted hydrogen generation. The enhanced HER performances are ascribed to the synergistic effects between Bi2 S3 and MoS2, giving rise to large electrocatalytic active area and fast HER kinetics. The results pave a new path to design and construct excellent Bi2 S3 /MoS2 nanomaterials for electrocatalytic hydrogen generation. Graphical abstract: Shown up are the polarization curves of as-fabricated materials in 1.0 M KOH electrolyte at a scan rate of 1 mV s −1 for electrocatalytic hydrogen evolution reaction. The inset presents the morphology of as-fabricated Bi2 S3 /MoS2 nanocomposites with the mass ratio of 5:5 between Bi2 S3 and MoS2 . Image 1 Highlights: Nanotremella-like Bi2 S3 /MoS2 catalysts are fabricated via a hydrothermal method. BMS-5 shows overpotential of 124 mV at 10 mA cm −2 for HER in 1.0 M KOH electrolyte. BMS-5 presents satisfactory long-term durability for continuous hydrogen producing.